Registro de actividad frugivora de aves en miconiasp. (melastomataceae) en el borde de bosque secundario en el Parque Nacional Natural Serranía de los Yariguíes (santader-colombia) - Peña Cañón, Ehidy Rocío; Rojas Sánchez, Adriana; Triana Balaguera, Erika Alexandra; Daza Criado, Ledy Angélica (Uptc, 2012)
In furtherance of this investigation, we observed bird species that visit and disperse the fruits of Miconia sp., reporting a total of twelve species of birds: Tangara arthus, Tangara nigroviridis, Tangara gyrola, Tangara parzudakii, Tangara cyanicollis, Tangara vitriolina, Tangara labradorides, Tangara vassorii, Tangara ruficervix, Anysognathus flavinucha, Tersina viridis and Euphonia xanthogaster, distributed in two families: Thraupidae and Fringilidae. It should be noted that Tersina viridis is a new report for Natural National Park Serranía Los Yariguíes. There was a greater number of visits between one and five in the afternoon. According to the data obtained, it follows that the duration of the visit is determined by several factors, among which is included the type of diet of the species, its collaboration and predation factors. Similarly, the success of the dispersion, reflected in the time of visit, is mainly affected by factors of seed predation.